Randomised study of EndoRings™-assisted vs. standard colonoscopy for detection of polyps in at risk individuals with Lynch Syndrome - Dhar, Rohin (Division of General Surgery, 2020)
Introduction: Lynch syndrome (LS) is an autosomal dominant condition and is the most common cause of inherited colorectal cancer (CRC), contributing to approximately 3%-5% of newly diagnosed cases of colorectal malignancy. LS affected individuals bear 18% – 53% lifetime risk for development of CRC. The only therapeutic approach to prevent development of CRC among individuals with LS is periodic colonoscopic screening for detection and removal of adenomas and polyps, which are the precursors for cancer. Despite being the current gold standard, and accounting for all other variables (such as experience of the physician), conventional colonoscopy has been known to sometimes miss detecting adenomas/polyps, specifically those present in the folds of the colonic mucosa and on the inner luminal wall of the colonic flexures. EndoRings™ assisted colonoscopy has therefore been developed to improve colonoscopy outcomes in terms of enhancing adenoma detection rates (ADR)/polyp detection rates (PDR) and involves flexible silicone rings mechanically stretching the colonic folds and thus enhancing total colon visualisation. Objectives: The present study aims to primarily investigate the efficacy of EndoRings™ assisted colonoscopy compared to traditional colonoscopy in terms of ADR/PDR in a known cohort of individuals with LS in a South African setting. Methods: The study was conducted as a cross-sectional randomised controlled trial. Individuals from the Northern Cape province of South Africa with LS were enrolled into the study during our Annual Northern Cape Colonoscopy Outreach trip for the year 2015. A total of 54 individuals (per-protocol) were included in the study and randomised blindly using computer randomisation into a control arm undergoing standard colonoscopy (n=27) and a study arm undergoing EndoRings™-assisted colonoscopy (n=27). Number of polyps detected (the primary outcome) along with a set of secondary outcomes was recorded in real time on data sheets for each individual and statically analysed using IPython. Results: The female to male ratio in the EndoRings™ group was 19:8 versus 15:12 in the standard colonoscopy group (P = 0.40) whereas the mean age of patients was 43.98±15.27 years and 44.26±14.67 years (P = 0.05) respectively. The average number of polyps detected in the EndoRings™ group was 1.4 versus 0.9 in the non-EndoRings™ group (P = 0.60). Conclusion: The present study outcomes observed comparable ADR/PDR in EndoRings™ assisted versus standard colonoscopy with no statistically significant difference. This result may be due to the study's limitations (small sample size) and design. Though no statistically significant conclusions could be reached, EndoRings™ assisted colonoscopy was perceived as being helpful in terms of increasing total colonic visualisation and allowing better scope stabilisation during interventions. Comparable intubation times, withdrawal times, total procedure times and similar complication rates were observed in both study arms. Although this study demonstrated non-inferiority of EndoRings™ compared to standard colonoscopy, further studies with a larger sample size in an easily accessible population over a longer study period are recommended.